Extracellular Vesicles Contribute to the Metabolism of Transthyretin Amyloid in Hereditary Transthyretin Amyloidosis - Yamaguchi, Hiroki; Kawahara, Hironori; Kodera, Noriyuki; Kumaki, Ayanori; Tada, Yasutake; Tang, Zixin; Sakai, Kenji; Ono, Kenjiro; Yamada, Masahito; Hanayama, Rikinari (Frontiers in Molecular Biosciences, 2022)
Hereditary (variant) transthyretin amyloidosis (ATTRv amyloidosis), which is caused by variants in the transthyretin (TTR) gene, leads to TTR amyloid deposits in multiple organs and various symptoms such as limb ataxia, muscle weakness, and cardiac failure. Interaction between amyloid proteins and extracellular vesicles (EVs), which are secreted by various cells, is known to promote the clearance of the proteins, but it is unclear whether EVs are involved in the formation and deposition of TTR amyloid in ATTRv amyloidosis. To clarify the relationship between ATTRv amyloidosis and EVs, serum-derived EVs were analyzed. In this study, we showed that cell-derived EVs are involved in the formation of TTR amyloid deposits on the membrane of small EVs, as well as the deposition of TTR amyloid in cells. Human serum-derived small EVs also altered the degree of aggregation and deposition of TTR. Furthermore, the amount of TTR aggregates in serum-derived small EVs in patients with ATTRv amyloidosis was lower than that in healthy controls. These results indicate that EVs contribute to the metabolism of TTR amyloid, and suggest that TTR in serum-derived small EVs is a potential target for future ATTRv amyloidosis diagnosis and therapy.